2011
DOI: 10.1007/s00244-011-9645-3
|View full text |Cite
|
Sign up to set email alerts
|

δ-Aminolevulinic Acid Dehydratase Single Nucleotide Polymorphism 2 and Peptide Transporter 2*2 Haplotype May Differentially Mediate Lead Exposure in Male Children

Abstract: Child low-level lead (Pb) exposure is an unresolved public health problem and an unaddressed child health disparity. Particularly in cases of low-level exposure, source removal can be impossible to accomplish, and the only practical strategy for reducing risk may be primary prevention. Genetic biomarkers of increased neurotoxic risk could help to identify small subgroups of children for early intervention. Previous studies have suggested that, by way of a distinct mechanism, δ-aminolevulinic acid dehydratase s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…Similar to the gender effects observed for ALAD 2 , at lowest levels of lead exposure, males but not females homozygous for hPEPT2*2 had significantly increased BLL (4.9 µg/dL vs. 2.6 µg/dL) (Sobin et al, 2011b). (Why hPEPT2*2 may be associated with higher blood lead burden in males has not yet been determined; possible explanations are discussed in the referenced manuscript).…”
Section: Introductionsupporting
confidence: 55%
See 3 more Smart Citations
“…Similar to the gender effects observed for ALAD 2 , at lowest levels of lead exposure, males but not females homozygous for hPEPT2*2 had significantly increased BLL (4.9 µg/dL vs. 2.6 µg/dL) (Sobin et al, 2011b). (Why hPEPT2*2 may be associated with higher blood lead burden in males has not yet been determined; possible explanations are discussed in the referenced manuscript).…”
Section: Introductionsupporting
confidence: 55%
“…Detailed procedures were previously described (Sobin et al, 2011a; Sobin et al, 2011b). Aggregate blood lead level was the mean of two values obtained an average of 60 days apart for each child.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies conducted with children exposed to ≤10 μg/dl of Pb from the environment, showed that blood Pb levels in boys were greater than that of girls and was exacerbated by a polymorphism in the gene encoding ALAD or PEPT2 [11]. …”
mentioning
confidence: 99%